Application of the precision eye health education model in myopia prevention and control in adolescents - Wang, Qi; Zhang, Lili; Wu, Yanmei (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to evaluate the application value and feasibility of a precise eye health education model in the prevention and control of myopia in adolescents.MethodsAdolescent students were assigned to either an experimental group or a control group, with both groups comprising one class from each of the seventh, eighth, and ninth grades across three schools. The experimental group received interventions based on the precision eye health education model, whereas the control group underwent a conventional health education program. One month after the intervention, assessments were conducted to evaluate students' eye health knowledge, attitudes, and practices (KAP), as well as their level of satisfaction with the format and content of the eye health education.ResultsA total of 461 students were included in the experimental group, while 443 students were in the control group. One month post-intervention, the experimental group demonstrated significantly higher scores in eye health knowledge, attitudes, and practices than the control group (P < 0.05). Additionally, students in the experimental group reported greater satisfaction with both the format and content of the educational intervention than those in the control group (P < 0.05).ConclusionThe application of a precision eye health education model for myopia prevention and control in adolescents effectively enhances students' knowledge, attitudes, and practices regarding eye health. Additionally, this model is associated with a high level of student satisfaction, highlighting its potential as a more effective approach to adolescent eye health education.